Algebraic Structures in Non-Commutative Geometry: An Exploration of Quantum Groups (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Non-commutative geometry offers a framework for studying spaces where the coordinates do not commute, extending classical geometric concepts into quantum mechanics and quantum field theory. A key algebraic structure within this framework is the quantum group, which serves as a quantum analogue of a Lie group, exhibiting distinct properties due to the non-commutative nature of its underlying algebra. This paper explores the role of quantum groups in non-commutative geometry, focusing on their algebraic structure, their relationship to deformation theory, and their applications in theoretical physics. In order to better understand how algebraic structures in non-commutative geometry can aid in the explanation of quantum phenomena, this work will look at both the mathematical characteristics and physical interpretations of quantum groups.